PENGEMBANGAN APLIKASI AUGMENTED REALITY BOOK PENGENALAN TATA LETAK BANGUNAN PURA GOA LAWAH DAN PURA GOA GAJA - Ni Komang Oktari Permata Sari; Padma Nyoman Crisnapati; Made Windu Antara Kesiman; I Made Gede Sunarya (Universitas Pendidikan Ganesha, 2014)
Goa Lawah and Goa Gajah Temple is two examples of temples in Bali, which have their own uniqueness. Goa Lawah Temple is located in Klungkung regency, especially inPasinggahan village in Dawan sub-district. One of its uniqueness is that the natural cave without human made, and it is a home for thousand bats. And then Goa Gajah Temple islocated in Bedulu village, in Blahbatuh district, Gianyar regency. This place is built in an ancient area. The cave in this place is different from Goa Lawah Temple. The cave in thisplace is built by human being. People believe that the T cave was built for meditation of theKings. Both of its temple is a part of cultural heritage wills we must to learn and preserve.There are so many methods to keep our culture. One of them is use Augmented Reality Technology.The purpose of this research is developing Augmented Reality applications an introduction the building layout of Goa Lawah and Goa Gajah Temple. In developing thisapplication, use Blender, Unity 3D and Vuforia Library to show 3 dimensional building inreality environment. This research using the waterfall model. The result of this research is a book that contains information and images related to Goa Lawah and Goa Gajah Temple andalso functioned as a marker of Book-based Augmented Reality applications android whichcapable of displaying objects of Goa Lawah and Goa Gajah Temple buildings in 3- dimensional form just above the marker complete with voice narration explanation. Thisapplication can be used as a medium to learn, introduce, at the same time preserving the GoaLawah and Goa Gajah Temple.